Diagnostics of load-bearing building structures of construction industry companies that operate under the influence of process liquids - Semko, Oleksandr; Avramenko, Yurii; Zyhun, Alina; Petrikei , Igor; Pleshynets, Artem (Academic journal Industrial Machine Building Civil Engineering, 2024)
Diagnosing load-bearing structures in construction industry enterprises exposed to technological fluids presents a unique set of challenges. These fluids, ranging from corrosive chemicals to abrasive slurries, can significantly accelerate the deterioration of concrete, steel, and other building materials. Effective diagnostics require a multi-faceted approach that considers the specific fluids involved, their concentration, temperature, and exposure duration. Visual inspections, supplemented by non-destructive testing (NDT) methods like ultrasonic testing, ground-penetrating radar, and impact-echo, are crucial for identifying hidden damage such as corrosion, cracking, and delamination. Furthermore, material sampling and laboratory analysis provide a definitive assessment of the extent of chemical attack and its impact on the structural integrity. Ultimately, a comprehensive diagnostic program enables informed decisions regarding repair, rehabilitation, or even replacement of affected structures, ensuring the safety and operational continuity of the enterprise.
Keywords: building structures; technical condition; reinforcement